Interpretatie van Zonnewijzerfragmenten (Bulletin KNOB, 1991)
This paper reaches after a framework to determination of patterns of hourlines on sundials on the basis of a complete, but broken sundial and a small fragment of another one, called Enthinge nr. 25 and nr. 16, after the manorial estate these sundials were excavated. Because of their unevenness fragments of slate sundials usually cannot be handled accurately.Reconstruction runs best with prints and transfer paper. When gnomic facts are missing, the auxiliary line, scratched in at the sundial's manufacture can help at determination. The hour-lines meet at the point of transition. Here the shadow caster is attached to the dial plate. This shadow caster, the style, must be directed to the polar star. The altitude of the pole above the horizon of a certain site can be derived from the atlas.Geographic latitude equals polar attitude. Thus sundials are tied down to their location. In case of the discovery of a cube-sundial several sundials are excavated at the same time. Sometimes remainders of sundials will be found, which do not match the here reached model, such as the declining of rotating sundial with the hands lying in between instead of exactly on the main wind directions.